Efektivitas Fumigan Sulfuryl Fluoride terhadap Pengendalian Tribolium Castaneum (Insecta : Coleoptera) di Gudang Industri Pakan Ternak di Wilayah Kota Semarang - Resita Oktianty (Jurnal Kesehatan Masyarakat (Undip), 2016)
Insect pests warehouse contained in commodities can affect the quality and quantity of the commodity. Every industry which has a commodity stored in warehouses makes efforts to prevent damage to the commodity. In this study to know the effectiveness of the fumigant sulfuryl fluoride in controlling Tribolium castaneum in the warehouse of animal feed industry. T. castaneum collected from warehouse of animal feed industry were tested.Application of fumigation using sulfuryl fluoride in the warehouse of animal feed industry is an attempt to control the commodity damage. The subjects were T. castaneum undertaken all insect life stages from eggs, larvae, pupae and adults of  T. castaneum. The results showed that there is a difference between mortality of T. castaneum at the stage of eggs, larvae, pupae and adults in the control group with mortality in the treatment group due to the use of sulfuryl fluoride fumigation treatment with a concentration of 24 g/m3 for 48 hours in the warehouse. This indicates that  fumigation application in warehouse of animal feed industry is effective to overcome the investment T. castaneum contained in commodities. However these fumigation activities are necessary to be prudence and must comply with existing rules especially following the SOP of the field condition. Efficiency and effectiveness of the fumigan of insect pest targeted should be considered.